Measuring Progress of Scrum-based Software Projects - Mahnic, V.; Zabkar, N. (Elektronika ir Elektrotechnika, 2012)
This paper describes a set of measures that provide IT management with continuous insight in the Scrum-based software development process. The proposed measures were applied within the scope of the project of rebuilding the web site of Slovenian daily newspaper with the highest circulation, which served as a case study for evaluation of their usability. The paper presents the measurement results and discusses their value for project management. The case study showed that each proposed measure describes a valuable process aspect and that data collecting does not require additional administrative work that would harm the agility of Scrum. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2630